2015
DOI: 10.1159/000440631
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Modified Substaging System (Kinki Criteria) for Patients with Intermediate-Stage Hepatocellular Carcinoma

Abstract: Introduction: Barcelona Clinic Liver Cancer (BCLC) stage B, an intermediate stage, includes various conditions of hepatocellular carcinoma (HCC). This heterogeneity of the patients with intermediate-stage HCC makes it difficult to predict their survival rates. In the present study, we examined the validity of the modified Bolondi classification (Kinki criteria) as a subclassification of patients with BCLC stage B HCC. Methods: Of 906 patients who underwent conventional transarterial chemoembolization at Kinki … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
0
35
2
Order By: Relevance
“…Substage B1 cases had a Child-Pugh score of 5-7 and met the up-toseven criteria; substage B2 cases had a Child-Pugh score of 5-7 and exceeded the up-to-seven criteria; substage B3 cases had a Child-Pugh score of 8-9 and any tumor status [20][21][22][23] .…”
Section: Kinki Criteriamentioning
confidence: 99%
“…Substage B1 cases had a Child-Pugh score of 5-7 and met the up-toseven criteria; substage B2 cases had a Child-Pugh score of 5-7 and exceeded the up-to-seven criteria; substage B3 cases had a Child-Pugh score of 8-9 and any tumor status [20][21][22][23] .…”
Section: Kinki Criteriamentioning
confidence: 99%
“…Our substaging that is based on the Bolondi's subclassification is simple and easy to use compared to the Bolondi's substaging. Previously, we reported that the Kinki criteria could be well stratified based on the survival in patients who underwent TACE [24]. In this study, we further evaluated the performance of the Kinki criteria in the HCC patients irrespective of the type of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This subclassification of intermediate-stage HCC recently became a well-discussed issue, and the Kinki criteria are used to subclassify patients with intermediate-stage HCC [12,13] . The OS of patients with B1, B2, and B3 HCC according to the Kinki criteria corresponds to that of patients with HCC of BCLC stages A, B, and C. In addition, patients with BCLC substage B2 HCC, especially those with multiple HCC tumors in both lobes, are not good candidates for TACE.…”
Section: Hcc (Bclc-c) Patients With Intermediate-stage Hcc (Bclc-b)mentioning
confidence: 99%